AGRICULTURAL AVIATION SAFETY FACTORS - Юн, Г. М.; Кандиба, Г. Ю. (Science-based technologies, 2013)
The article considers the factors which affects to the safe operation of agricultural aviation. Ability of use small aircraft and pesticides to acts of bioterrorism and terrorism, analyzed agricultural aviation events and disasters in Ukraine and CIS. Agricultural terrorism is deliberate or intentional improper handling of agricultural chemicals, aircraft or inventory for damage to third parties or property. Agroterrorism is the using of chemical or biological weapons against agriculture or food industry. The problem is that the aircraft can be used as a tool of assassination. Factors that affect the safe operation of aircraft in the performance of air chemical processing. Modern agriculture has features that make it vulnerable to terrorist attacks. As a result, chemicals and infectious pathogens may be intentionally added to any level of the continuous cycle of agricultural production. On the example of the United States analyzed the possible danger of using agricultural aircraft and pesticides in order to terrorist attacks.